Floating Teeth Appearance: A Diagnostic Radiographic Alarm - Mortazavi, Hamed; Safi, Yaser; Khalighi, Hamid Reza; Forouzani, Gelareh; Behnaz, Mohammad (Regeneration, Reconstruction & Restoration (Triple R), 2020)
Introduction: Floating teeth is a condition when teeth lose their supporting alveolar bone as a result of a destructive process, which is most frequently occur in the molar/ premolar region of both jaws. The aim of this study was to review the common conditions associated with floating teeth. Materials and methods: We used general search engines and specialized databases including Google Scholar, Pub Med, Pub Med Central, Science Direct, and Scopus to find relevant studies by using keywords such as "jaw lesion", "jaw disease", "floating tooth", “floating teeth”, "tooth mobility", and “tooth loss”. About 100 articles were found, of which approximately 80 were broadly relevant to the topic, and finally 30 articles closely related to the above topic were chosen. Results: When the data were compiled, the following 9 lesions were found to have more relationship with floating teeth appearance: Aggressive periodontitis, Langerhans histiocytosis, Burkitt’s lymphoma, multiple myeloma, Metastatic tumors, Primary intraosseous carcinoma (intraosseous squamous cell carcinoma), Ewing’s sarcoma, Hyperparathyroidism, and Cherubism. Conclusion: When clinicians encounter a lesion associated with floating teeth, they should consider these entities especially malignant disorders in differential diagnosis to make more accurate diagnoses and develop better treatment plans according to patients’ imagings.